Problem-based Learning (PBL): A Teaching Strategy of Environmental Education, in Cañete Municipal School Students - Paredes-Curin, Carlos Rodolfo (2016)
This article aims to “analyze the elements of the learning process that emerge in high school freshman students at Liceo Alonso de Ercilla y Zúñiga, through the methodology of problem-based learning (PBL) on issues of environmental education, specifically in the unit of photosynthesis”. The choice of participants was made by convenience; they are 15 years old on average, regardless of gender or age, and belong to freshman high school level. The focus of this research is qualitative, since it seeks to recognize the significance of social facts in their context to rebuild them. This approach, along with the constant comparative method, ethnographic study, techniques for collecting and analyzing data (such as open interview, observation and triangulation, and under the aegis of the descriptive paradigm), resulted in students improving their self-learning skills, as they collected information, studied, organized and presented results, given that the PBL allowed to reflect on their successes and failures and improved their learning as they learned and inquired more on the topic of photosynthesis.